Modelagem Computacional para Avaliação Preliminar do Potencial de Correntes de Maré no Canal do Boqueirão - COSTA, Aline Mayara Santos (2022)
Tidal energy is an alternative source for generating electricity. Hence, the utilization of the energy potential of the oceans represents an approach to produce clean energy without impacting the environment. Brazil presents a notable tidal potential, mainly on the coast of the North Region, which comprises the states of Amapá and Pará, and the coast of the Northeast Region, covering only the state of Maranhão. The Boqueirão Channel, located in the São Marcos Bay, in Maranhão, is recognized for its major sea level variation and strong tidal currents, which denotes a large potential of tidal currents. Thus, this work proposes a computational modeling for preliminary assessment of the potential tidal currents in the Channel. In loco measurements were also carried out, and the data collected were used for model calibration, characterization of the study area, and analysis of the results, which compared measured and simulated data. A result, it was possible to obtain curves to estimate the annual energy potential. The estimate of the energy potential by the hydrodynamic model in the Boqueirão Channel region was 1.7992 GWh/year.